Disinfection and reuse of N95 respirators during the COVID-19 pandemic - Victor Marcel Aguilar Salas; Eleana Victoria Benavides Febres (Editorial Ciencias Médicas, 2022)
Introduction: We are living in a context of COVID-19 pandemic, where the shortage of personal protective equipment in health is evident and it is expected that it will continue in the short and medium term. So, considering the reuse or prolonged use of some personal protective equipment, especially respirators, could be an alternative to consider. Objective: To review and disseminate, based on scientific evidence, different forms of disinfection in order to safely and affordably reuse N95 respirators. Main comments: N95 respirators or their equivalents are for the exclusive use of health personnel for the care of patients with suspected or confirmed COVID-19 and in aerosol generation procedures. Its effectiveness depends to a large extent on the condition of the respirator, the filtration capacity, the sealing and its proper use. There are several methods to disinfect, such as ultraviolet light type C, hydrogen peroxide, dry and humid heat, ozone, microwave irradiation, etc. If these procedures are not performed properly, they may not be effective. Global feedback: In personal protective equipment shortage scenarios, reuse is a viable, economical, safe, potentially scalable and easy-to-perform procedure. N95 respirators require a special disinfection procedure to preserve their filtration and sealing capacity. There are a limited number of disinfection and reuse cycles. Dry heat stove might be the most affordable method in private settings.